Experimental Investigation of Self-compacting High Performance Concrete Containing Calcined Kaolin Clay and Nano Lime - Akram Obeed Kadhum; Haider M. Owaid (Civil Engineering Journal, 2020)
The aim of this research is to investigate the effect of pozzolanic materials and nano particles on improve the strength characteristic by the properties of a self-compacting high-performance concrete that includes calcined clay with nano lime. In this study, two blends systems are worked on, they are the binary and the ternary systems. For binary mixtures, test samples were prepared from 5% CC, 10% CC, 15% CC and 3% NL by partial replacement of the cement weight. While ternary mixtures, samples were prepared from 5% CC 3% NL, 10% CC 3% NL and 15% CC 3% NL by partial substitution of cement weight. The tests conducted on mixes are fresh tests like slump flow diameter, V-funnel, L-box, and segregation resistance. The compressive strength test was determined at 7, 28 and 56 days. While splitting tensile strength tests at 7 and 28 days from the SCHPC produced in the study. It was concluded that the replacement of CC and NL in SCHPC binary mixes reduced the fresh results enough for SCHPC production and gave a general improvement in the compressive strength and splitting tensile strength properties of the SCHPC mixture. SCHPC with 10% CC partial replacement of cement showed higher values of compressive and splitting tensile strength, compared to the reference mixture of SCHPC for all days, thus it was considered the best. Whereas, the strength of the concrete mixtures in the ternary cement mixtures was better than the strength of the mixing and control mortar systems for the same replacement levels in 7 , 28 and 56 days.